Inverse Association between Dietary Intake of Selected Carotenoids and Vitamin C and Risk of Lung Cancer - Shareck, Martine; Rousseau, Marie-Claude; Koushik, Anita; Siemiatycki, Jack; Parent, Marie-Elise (Frontiers in Oncology, 2017)
While diets rich in fruit and vegetables appear to reduce lung cancer risk, the evidence for individual carotenoid and vitamin intakes has been judged too limited to reach firm conclusions. Data from a case–control study of lung cancer (Montreal, QC, Canada, 1996–2002) were used to investigate the role of dietary intakes of β-carotene, α-carotene, β-cryptoxanthin, lutein/zeaxanthin, lycopene, and vitamin C in lung cancer risk. In-person interviews elicited dietary information from 1,105 incident cases and 1,449 population controls. Usual frequency of consumption of 49 fruits and vegetables 2 years prior to diagnosis/interview was collected. Odds ratios (ORs) and 95% confidence intervals (CIs) between intake variables and lung cancer were estimated using logistic or polytomous regression, adjusting for potential confounding factors including a detailed smoking history. ORs associated with upper versus lower tertiles of intake were 0.66 (95% CI = 0.51–0.84) for β-carotene, 0.70 (95% CI = 0.55–0.90) for α-carotene, 0.65 (95% CI = 0.51–0.84) for β-cryptoxanthin, 0.75 (95% CI = 0.59–0.95) for lycopene, and 0.74 (95% CI = 0.58–0.96) for vitamin C. ORs suggestive of a protective effect were found for elevated intakes of β-carotene, α-carotene, β-cryptoxanthin, and lycopene in male heavy smokers and of vitamin C in female heavy smokers. Selected antioxidants were also associated with a lower risk of lung cancer in female moderate smokers, and of squamous cell carcinoma, adenocarcinoma, and small cell carcinoma. These results suggest that several dietary antioxidants found in common food sources may protect against lung cancer, even among heavy smokers.